Common Causes of Donor Rejection in Blood Transfusion Services at Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh (Community Based Medical Journal, 2025)
A cross-sectional, descriptive study was carried out in the Department of Transfusion Medicine of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between April 2008 and March 2009, to determine common causes of donor rejection in blood transfusion services. From the register book of the department data was curated. A total of 16,619 donors were included in data analysis. Among them, a total of 765 were rejected donors: party donor and voluntary donor were 558(73%) and 207(27%) respectively. The majority of the rejected donors were in 18-30 years age group (68%), followed by 31-40 years age group (24.2%), 41-60 years age group (5.9%), 60-65 years age group (0.7%). In sex distribution, 603(78.8%) were males and 162(21.2%) were females; male-female ratio was 3.7:1. The majority of the study subjects belonged to the 18-30 years age group (68%), followed by 31-40 years age group (24.2%), 41-60 years age group, >60 years age group (0.7%). Most of the donors were students (40.8%); among females most of them were housewives. Party donor and voluntary donor rejection 558(73%) and 207(27%) respectively. Donor rejection was due to medical causes 443(57.9%), serological causes 207(27.1%) and non-medical causes 115(15.0%). Among medical causes, history of sensitive/contraindicated medication 98(12.8%), ongoing menstruation 37(4.8%), history of jaundice 26(3.4%) and asthma 21(2.7%) were common. Among non-medical causes, 100(13.1%) were rejected due to short interval from previous blood donation, while 10(1.3%) were rejected due to underage (65). Among physical findings, 101(13.2%) of were rejected due to underweight, 27(3.5%) due to high blood pressure, 17(2.2%) due to low blood pressure, 21(2.7%) for low hemoglobin levels and 13(1.7%) allergic skin conditions. Donor rejected for serological causes involved 188(24.6%) HBsAg positive and 19(2.5%) HCV positive cases.  CBMJ 2025 January: Vol. 14 No. 01 P: 34-39